Proyecto de factibilidad para la creación de una empresa organizadora de eventos sociales en el cantón Gonzanama, provincia de Loja, para el año 2015 - Díaz Cango, Andreina Paola (2017)
This research topic called "PROJECT FEASIBILITY FOR THE CREATION OF A SOCIAL EVENT ORGANISER IN CANTON Gonzanamá, Loja province, by the year 2015", is an initiative that arises from the lack of jobs, low implementation of SMEs which can be used in place of existing natural, material and human resources, has become one of the most critical aspects, becoming due at a high socio-economic problem that causes a deterioration in the quality of life of its inhabitants. What it has been of utmost importance to investigate the issue proposed as an alternative that will contribute to the development of the province of Loja, especially the canton Gonzanamá. The lack of a meeting room in the canton Gonzanamá is causing discomfort among the local population, organization and enjoy all kinds of social, cultural event of a political nature such as sports, as the premises where such events made no They feature comfortable, adequate and secure infrastructure that meets your needs and expectations. In developing this investment project, a literature review about basic concepts related to the development of investment projects was held at first instance. Also reference is made visual analysis it yielded information that exist do not pay local conditions and facilities for this kind of event information that is found to the implementation of the surveys. Different methods and techniques used in the research process were the scientific method, inductive method, deductive method, statistical method, as a technique direct observation was used, the survey by reference to a population to be surveyed 374 people, later made the tabulation and interpretation of the results to the applicants, as well as the analysis of the information obtained from the surveys of potential bidders they were also used to reach conclusions, and recommendations. In the market analysis it was determined that there is a surplus of 21,354 events effective potential demand, with an offer of 1,296 and has an unmet need for 20,058 events per year. The main competitors for the new project are: D, Vicky events, Moon events, and providing almost the same services to render the new company other local competition would not be as it is today banned the provision of premises for this kind of events referring to colleges and schools. By analyzing various market strategies and marketing tactics aimed at marketing mix (product, price, place and promotion) to enable it to position itself as a leader in organizing events in the Canton province of Loja Gonzanamá raised. The technical study, the size and location of the company is analyzed, production capacity installed and used, as well as the best location within the county, which is in the central district Av. September 30 and San Pedro Street corner, being a strategic position to generate income as the influx of people in this sector, it is busy. Within the administrative research company to determine it’s organic, functional structure, legal and organizational basis to determine roles and responsibilities of each of the elements that constitute also organizational, structural, functional and positional were built and their manual functions for each of its members. Concluding with financial analysis, in the calculation of the necessary resources and sources of funding necessary required for the installation and operation of the company, determining a total investment is $ 33.619,94, the company is expected to have an average income for the first year $ 130.750,35 These figures are supported by the respective budgets. To demonstrate the feasibility of the project made use of financial indicators such as net present value (NPV) which is $ 4.893,03; Internal Rate of Return (IRR) 14.30%; Benefit Cost Ratio (B / C) 1.10% Capital Recovery Period (PRC) 6 years 8 months 19 days, showing that the project is feasible to be done therefore is suitable implementation, the coefficient of sensitivity increase in costs is 5.24% is 0.99 and with a decrease in revenue of 4.77% which is 0.99 which shows that is not sensitive to change and does not affect profitability. Getting itself to the following conclusions: that if its implementation is feasible, since the results show a significant return for entrepreneurs, with an effective demand for 21,354 social events a year, with an offer of 1,296 social events each year, settling a lawsuit 20,058 unmet social events a year , the company aims to cover 3.63 % of unsatisfied demand, it was located in Region 7 province of Loja , canton and city of Gonzanamá , swept Central Av . September 30 and street San Pedro corner, for which the company will use latest technology machinery to guarantee the same quality of it. It also raised the following recommendations: that the project is executed because besides being profitable generate jobs, reducing unemployment in the canton Gonzanamá, entrepreneurs and investors are supported by these studies in order to reduce investment risks, which acquires a software, it would serve you to maintain greater control of income and expenditure of the raw material and have control of costs and profits, the company realizase ongoing advertising campaigns possession better in the minds of potential customers, which through government implementation of this kind of exonerating projects support in the early years of paying taxes because many times this projects are stopped by the existing as complicated procedures, high tariff payments more than their high bank lending. With the study mood, economic and social was determined to be negative environmental impact that the company would cause to the environment, on the other hand is very positive in the social and economic spheres since it will create jobs by reducing rates poverty in the canton Gonzanamá.